Dathlu! - Cadwaladr, Rhian (Gwasg Carreg Gwalch, 2022)
On the eve of their 60th birthdays, four lifelong friends venture on a special journey. As their lives have all been in complete contrast to one another, will the celebration turn bitter?.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books